Modernization and diversification of a sustainable labor system in the economy - Tursunova Aziza, (THE INNOVATION ECONOMY, 2026)
The article analyzes the essence of the concept of economic growth, its types, analysis of factors affecting the rate of economic growth, definitions of economic growth, the essence and necessity of implementing economic reforms. Taking into account the above, the current state of the country's growth was analyzed. Thus, the main focus of this article is on the importance of economic growth factors, that is, their contribution to the country's gross domestic product